Effects of ionizing radiation on bone neoformation: histometric study in Wistar rats tibiae - Lucatto,Susette Cavicchioli (2011)
PURPOSE: Comparing the ionizing radiation effects on bone neoformation of rats tibiae previously submitted to radiotherapy with a single dosage of 30Gy with the contralateral tibiae that have received secondary radiation. METHODS: In thirty male Wistar rats, 30 days before surgical procedure when round defects would be created on the bone, the right tibia was irradiated with 30Gy and the left tibia received a calculated secondary radiation dose of 7Gy. Sacrifices were performed after 4, 7, 14, 21, 56 and 84 postoperative days and both tibiae were removed for histological processing. RESULTS: The left tibiae that received the dose of 7Gy has shown more bone neoformation from 14th postoperative days, giving evidences of less damage to cellular population responsible by bone neoformation. On the other hand, the dose of 30Gyon right tibiae did not exhibit significant differences among the periods, suggesting damage of long-lasting or even permanent duration. CONCLUSION: Tibiae submitted to radiation dose of 30Gy have shown more damage to bone cells than tibiae that received secondary radiation dose of 7Gy, especially observed on 14th, 56th and 84th postoperative days.